Temporal control in chained fixed-ratio, fixed-interval schedules - Todorov, João Claudio (2017)
Four rats were subjected to chained fixed-ratio (FR), fixed-interval (FI) schedules of reinforcement (chain FR 5 FI). A FR schedule at one lever produced a discriminative stimulus (i.e., light) associated with an FI schedule of primary reinforcement (water) at the second response lever. The FR schedule was kept constant, whereas the FI length was changed from 10 to 60 s under five different experimental conditions. Increases in the FI length resulted in increases in pre-ratio pauses, but pauses in the FI tended to be a constant percentage of FI length. Data from this experiment indicate that pre-ratio pauses are also a function of the interreinforcement interval (IRI). Data from three experiments with chained FR 5 FI 60-s schedules indicate that pausing in the FI component of chained FR FI schedules with the FI as the second component of the chain may tend to disappear as the IRI duration increases.